Daratumumab with lenalidomide and dexamethasone in relapsed or refractory multiple myeloma patients - real world evidence analysis - Stork, Martin; Spicka, Ivan; Radocha, Jakub; Minarik, Jiri; Jelinek, Tomas; Jungova, Alexandra; Pavlicek, Petr; Pospisilova, Lenka; Sedlak, Frantisek; Straub, Jan; Pika, Tomas; Knechtova, Zdenka; et al. (Annals of hematology, 2023)
We performed real world evidence (RWE) analysis of daratumumab, lenalidomide and dexamethasone (Dara-Rd) versus lenalidomide and dexamethasone (Rd) treatment in relapsed/refractory multiple myeloma patients (RRMM). In total, 240 RRMM patients were treated with Dara-Rd from 2016 to 2022 outside of clinical trials in all major Czech hematology centers. As a reference, 531 RRMM patients treated with Rd were evaluated. Patients' data were recorded in the Czech Registry of Monoclonal Gammopathies (RMG). Partial response (PR) or better response (ORR) was achieved in significantly more patients in Dara-Rd than in Rd group (91.2% vs. 69.9%; p < 0.001). The median progression free survival (PFS) was 26.9 months in the Dara-Rd and 12.8 months in the Rd group (p < 0.001). Median overall survival (OS) was not reached in the Dara-Rd compared to 27.2 months in the Rd group (p = 0.023). In patients with 1-3 previous treatment lines, there was significant PFS benefit of Dara-Rd compared to Rd (median PFS not reached vs. 13.2 months; p < 0.001). In patients with > 3 previous treatment lines, there was no significant PFS benefit of Dara-Rd treatment (7.8 months vs. 9.9 months; p = 0.874), similarly in patients refractory to PI + IMIDs (11.5 months vs. 9.2 months; p = 0.376). In RWE conditions, the median PFS in RRMM patients treated with Dara-Rd is shorter when compared to clinical trials. In heavily pretreated RRMM patients, efficacy of Dara-Rd treatment is limited; best possible outcomes of Dara-Rd are achieved in minimally pretreated patients.
Keywords: Lenalidomide; Antineoplastic Combined Chemotherapy Protocols; mnohočetný myelom; protokoly protinádorové kombinované chemoterapie; Dexamethasone; Humans; Multiple Myeloma; dexamethason; lenalidomid; lidé